PENGARUH KUALITAS JASA DAN DIGITAL MARKETING TERHADAP MINAT BELI KONSUMEN CAPTURE STUDIO PEKANBARU - Zainol Fuady; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at Capture Studio Pekanbaru which is located on Marsan Sejahtera Street, Sidomulyo Barat, Tampan, Pekanbaru. The problem in this study is that in the last five years the company has only reached one target and even a decline in income in the last two years. The purpose of this study was to determine the effect of service quality and digital marketing on consumer buying interest in capture studio Pekanbaru. In this study the method used was quantitative descriptive with the SPSS program. The population in this study were consumers who used services from capture studio Pekanbaru, which amounted to 408 consumers. Samples taken based on the method using the Slovin formula are 80 respondents. Hypothesis testing uses a simple linear regression analysis method and multiple linear regression analysis with the results showing that the quality of services and digital marketing have a significant effect on consumers' interest in buying capture studio Pekanbaru. With a simple calculation of the coefficient of determination (R2) of service quality on consumer buying interest, the value of R Square of 0.646 or 64.6% and digital marketing towards consumer buying interest obtained values of 0.666 or 66.6% and the calculation of determination (R2) was obtained R Square of 0.756 or 75.6%. This shows that the quality of services and digital marketing have an influence of 75.6% on consumers buying interest in capture studio Pekanbaru, while the remaining 24.4% is influenced by other variables not examined in this study.Keywords: Service Quality, Digital Marketing, Consumer Buying Interest.